The Effectiveness of Nutrition Education about Local Specific Food-based Balanced Nutrition Recommendation on Dietary Intake Level and Anemia Status in Female Adolescents at the Hidayatullah Arrohmah Islamic Boarding School Malang - Mustafa, Annasari; Rizky Maulidiana, Annisa (KnE Life Sciences, 2019)
Background: Anemia is the biggest nutritional problem in Indonesian adolescents. One of the main risk factors is poor diet. Nutrition education as an intervention method has been shown to significantly improve healthy lifestyle and academic achievement in school-aged children. Objective: To analyze the effectiveness of nutrition education about local specific food-based balanced nutrition recommendation on the knowledge, dietary intake level, and anemia status of female adolescents. Methods: This study was a quasi-experimental research with pre- and post-test design. Eighty-three female students of the Hidayatullah Arrohmah Islamic Boarding School Malang were included as study participants. The nutrition education in the form of class counseling on balanced nutrition guidelines and healthy snacks was given for five consecutive months. Dietary consumption, knowledge, and hemoglobin level were measured before and after the intervention. Data analysis was done using paired t-test and Wilcoxon signed-rank test with p<0.05 considered as significant. Results: There was a significant difference of the protein (p=0.029) and Fe (p=0.021) intake level before and after the intervention, however, this result was not found in the vitamin C and folic acid intake. The nutritional knowledge as well as the hemoglobin level were increased significantly (p=0.001, p=0.04, respectively). Conclusions: Nutrition education about local specific food-based balanced nutrition recommendation is very effective to increase knowledge, dietary intake (protein and iron), and hemoglobin levels in female adolescents.